Keindahan Tilawah Al-Qur’an Dalam Empat Dimensi Estetika Al-Ghazali - Helda Pauziah (JOURNAL SAINS STUDENT RESEARCH, 2025)
Recitation of the Qur’an (Tilawah) is not only a religious practice but also an artistic expression containing profound aesthetic values. This study aims to explore the beauty of Qur’anic recitation through Al-Ghazali’s four-dimensional aesthetic framework: ilāhiyyah (divine), ‘aqliyyah (rational), qalbiyyah (spiritual), and ḥissiyyah (sensory). Employing a qualitative descriptive approach, data were collected from literature review of classical and contemporary sources on Qur’anic recitation and Al-Ghazali’s writings. The findings reveal that the harmony between melodious recitation and correct tajwīd embodies both sensory and spiritual beauty, bridging intellect, emotion, and faith. Tilawah thus functions as a multidimensional practice that purifies the soul (tazkiyah al-nafs) and strengthens the reader’s connection with Allah. The study highlights the integration of sound, meaning, and devotion as central to the aesthetic experience of Qur’anic recitation.